Anxious Attachment Mediates the Associations Between Early Recollections of Mother's Own Parental Bonding and Mother–Infant Bonding: A 2-Month Path Analysis Model - Kalfon Hakhmigari, Maor; Peled, Yoav; Krissi, Haim; Levy, Sigal; Molmen-Lichter, Maayan; Handelzalts, Jonathan E. (Frontiers in Psychiatry, 2021)
Parental bonding (recollection of own parents' parenting), adult attachment, and mother-infant bonding, are all closely-related yet distinct concepts of the parent-child relationship, sometimes used interchangeably in the literature. This study aimed to examine the associations between these concepts in a longitudinal path analysis design. 262 postpartum women who gave birth at the maternity ward of a large tertiary health center in Israel completed a demographic questionnaire, the Experiences in Close Relationships Scale, and the Parental Bonding Instrument (PBI) at 1–4 days postpartum, and the Postpartum Bonding Questionnaire (PBQ) at 2 months postpartum. Parental care factor (PBI) was found to be associated with mother-infant bonding (PBQ), directly and indirectly through insecure anxious attachment. Denial of autonomy factor (PBI) was found to be associated with mother-infant bonding only through insecure anxious attachment. Encouragement of behavioral freedom factor (PBI) was found to be associated with mother-infant bonding (PBQ) in a simple correlation but not in the complete model. The results highlight the intergenerational aspects of parenting and suggest that early childhood interventions with parents may have a long-term impact on childrearing though generations, and by that on children’s development.